Article 8(2) of the federal constitution and gender equality in Malaysia: a critical analysis of its effectiveness over gender discrimination against women and suggestion to reform / Ahmad Tanzil Mohd Nasser … [et al.] - Mohd Nasser, Ahmad Tanzil; Mohd Khairi, Muhd Muqrib; Mohd Fauzi, Muhamad Syahrul Asyraf; Che Harun, Mohammad Zarul Farrid (2014)
The gender equality issue remains as a serious problem in Malaysia. Several efforts had been made by the government to limit gender equality problems. However, this problem had not come to the ends yet despite Act and regulation has been amended and some efforts from the government and non-government organization (NGO). Thus, this research is to show gender equality situation in Malaysia and compare it to other countries and suggest some reformation that this country should consider. This research has five chapters. The first chapter consists of the introduction and research backgrounds which explain about the meaning of gender equality, the law in relation with gender equality in Malaysia and in comparison with the law of gender equality in United States of America (USA) and the Philippines. Apart from that, it also contains the objective, problem statement, research methodology, scope of research, and limitations of research that we encounter in doing this research. Generally, Chapter 2 is the literature review about the gender equality law in Malaysia and the problem with the existing law was also highlighted. While in Chapter 3 consists of the law review on the gender equality law in United States of America (USA). Next in Chapter 4, it consists of gender equality law in the Philippines. These countries were used as a reference and comparison to the gender equality law and problems that had been exercise and happen in Malaysia. In Chapter 5 which is the last chapter, there were a few recommendations to shift our current gender equality situation to the approach as practice by United States of America (USA) and the Philippines. It also suggests the implementation of new law or Act to improve the gender equality situation in Malaysia.